2010
DOI: 10.21273/horttech.20.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge, Gaps, and Future Needs for Keeping Water and Nutrients in the Root Zone of Vegetables Grown in Florida

Abstract: The success of the best management practices (BMPs) program for vegetables in Florida is measured by the level of BMP implementation and the improvement of water quality. Both require keeping water and fertilizer in the root zone of vegetables. The University of Florida Institute of Food and Agricultural Sciences (UF/IFAS) Extension Vegetable Group has identified the fundamental principles of 1) basing UF/IFAS production recommendations on the rigors of science and the reality of field production; 2) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 57 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…A study by Zotarelli et al (2009a) in Citra, FL, reported similar interannual differences in tomato yields when rainfall was greater along with higher temperatures in the middle of the growing season. Improving irrigation scheduling based on soil moisture sensors and crop needs will help reduce nitrate leaching in field tomato production in sandy soils (Simonne et al, 2010;Zotarelli et al, 2009b). In this study, significant yield improvement was generally not oberved with N rates above 168 kg · ha -1 .…”
Section: Discussionmentioning
confidence: 69%
“…A study by Zotarelli et al (2009a) in Citra, FL, reported similar interannual differences in tomato yields when rainfall was greater along with higher temperatures in the middle of the growing season. Improving irrigation scheduling based on soil moisture sensors and crop needs will help reduce nitrate leaching in field tomato production in sandy soils (Simonne et al, 2010;Zotarelli et al, 2009b). In this study, significant yield improvement was generally not oberved with N rates above 168 kg · ha -1 .…”
Section: Discussionmentioning
confidence: 69%
“…Due to the low NUE of potato, fertilizer application method, inefficiency of the irrigation system, and soil type, increased N fertilizer rates may be necessary to compensate for N losses, especially after intense rainfall (Simonne et al, 2010). In recent years, many potato growers in northeastern Florida have adapted to banding fertilizer instead of broadcast application.…”
mentioning
confidence: 99%
“…Development of best management practices (BMPs) for nutrient management should take into consideration fertilizer rates, the timing of applications, fertilizer sources, and placement (Simonne et al, 2010). In addition, irrigation management in shallow water table soils plays an important role in soil N movement.…”
mentioning
confidence: 99%